2011
DOI: 10.9708/jksci.2011.16.12.215
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Information Security against Cyber Attacks in Universities and Its Improvement Methods

Abstract: This paper suggests several methods of improving information securities of universities through the investigations of the current status of information securities in universities, which is becoming a hot topic in knowledge and information societies. In this paper, universities were randomly selected according to their size, and surveyed through email questionnaire to the persons in charge of security in each university, and 27 universities and 18 colleges were replied. From the survey results we confirmed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Chapman 5 and Coughlan 6 observed that some of the cyberattacks targeted at universities are carried out by students just to prove to their fellow peers that they are computer wizards and in some cases to steal sensitive information. According to Kang and Choi, 7 universities and colleges are the prime targets for cyberattacks because most institutions of higher learning have their networks open to enable students and employees access from within and outside university local area networks.…”
Section: Introductionmentioning
confidence: 99%
“…Chapman 5 and Coughlan 6 observed that some of the cyberattacks targeted at universities are carried out by students just to prove to their fellow peers that they are computer wizards and in some cases to steal sensitive information. According to Kang and Choi, 7 universities and colleges are the prime targets for cyberattacks because most institutions of higher learning have their networks open to enable students and employees access from within and outside university local area networks.…”
Section: Introductionmentioning
confidence: 99%